Стереотип національного характеру українців у прозових жанрах фольклору - Ляшук, Наталія; Lyashuk, Natalia (Східноєвропейський національний університет імені Лесі Українки, 2016)
Стаття присвячена вивченню етнічних стереотипів українців у прозових жанрах фольклору, зокрема в казках, легендах, прислів’ях і приказках. Проведено аналіз мовних засобів вираження етнопсихологічних якостей українців, що формують етнічний стереотип. Стверджено тяжіння автостереотипів до позитивності в оцінюван національних рис характеру. The article deals with the investigation of the Ukrainians’ ethnic stereotypes in the folk prose: fairy tales, legends, proverbs and sayings. The article presents the analysis of the language means aimed at creating ethnic spirit and psychological nature of the Ukrainians which actually reflect the ethnic stereotypes . The article highligts specificity of creating the lexical and semantic image structure in the epic folk works. The author reveals the polysemantic function of the folk images and the expression of the ethnic and psychological features of the Ukrainians by generalizing traditional structures of the fairy tales. It is emphasized that the authors of the legends verbalize the stereotype character features mostly by means of the direct meaning of the lexeme. The biggest set of the Ukrainians’ nominations can be found in the proverbs and sayings including both the positive character features of the human being and the negative ones. The study has proved that there is a tendency to auto-stereotypes positivity in assessing national qualities of character.
The Ukrainians’ National Character Stereotype in the Prose Genres of Folclore
Keywords: етнічний стереотип; стереотип національного характеру; автостереотип; прозові жанри фольклору; ethnic stereotype; auto stereotype; national character; folk prose